Handbook of Research on Improving Engineering Education With the European Project Semester - Malheiro, Benedita (2022)
Engineering education aims to prepare engineering undergraduates for their future professional journey where they will be called on to solve challenges affecting individuals, companies, and society. The European Project Semester (EPS) exposes students to project- and challenge-based learning, paying special attention to international multidisciplinary teamwork, sustainable design, innovative thinking, and project management in order to develop a set of desired professional skills. The Handbook of Research on Improving Engineering Education With the European Project Semester shares the best practices in engineering education through close examination of the EPS. It describes the adopted learning framework, analyzes how it contributes to the development of skills, reports on the types of challenges proposed to teams, and delivers a set of team-project cases from the network of providers. Covering topics such as engineering ethics, project management, and sustainable behavior, this book is essential to students in engineering, engineers, engineering educators, educational researchers, academic administration and faculty, and academicians.